Crotofolane‐ and Casbane‐Type Diterpenes from Croton argyrophyllus. Issue 6 (19th June 2013) - e Silva Filho, Francisco Artur; Nunes da Silva Junior, José; Braz‐Filho, Raimundo; de Simone, Carlos Alberto; Silveira, Edilberto Rocha; Lima, Mary Anne Sousa
Abstract Phytochemical analysis of Croton argyrophyllus led to the isolation of five new diterpenes named (5β, 6β)‐5, 6 : 13, 16‐diepoxycrotofola‐4(9), 10(18), 13, 15‐tetraen‐1‐one (1), (5β, 6β)‐5, 6 : 13, 16‐diepoxy‐2‐epicrotofola‐4(9), 10(18), 13, 15‐tetraen‐1‐one (2), (5β, 6β)‐5, 6 : 13, 16‐diepoxy‐16‐hydroxy‐2‐epicrotofola‐4(9), 10(18), 13, 15‐tetraen‐1‐one (3), (5β, 6β)‐5, 6 : 13, 16‐diepoxy‐16‐hydroxy‐2‐epicrotofola‐4(9), 10(18), 13, 15‐tetraen‐1‐one (4) and (2E, 5β, 6E, 12E)‐5‐hydroxycasba‐2, 6, 12‐trien‐4‐one (5), in addition to the known diterpenes crotonepetin and depressin, and acetylaleuritolic acid and spinasterol. The structures of the isolated compounds were established by a combination of spectroscopic methods, including HR‐ESI‐MS, 2D‐NMR, and X‐ray crystallography.